2007
DOI: 10.1038/nn1826
|View full text |Cite
|
Sign up to set email alerts
|

Properties of basal dendrites of layer 5 pyramidal neurons: a direct patch-clamp recording study

Abstract: Basal dendrites receive the majority of synapses that contact neocortical pyramidal neurons, yet our knowledge of synaptic processing in these dendrites has been hampered by their inaccessibility for electrical recordings. A new approach to patch-clamp recordings enabled us to characterize the integrative properties of these cells. Despite the short physical length of rat basal dendrites, synaptic inputs were electrotonically remote from the soma (>30-fold excitatory postsynaptic potential (EPSP) attenuation) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
474
4
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(517 citation statements)
references
References 48 publications
35
474
4
4
Order By: Relevance
“…The present study shows that clustered input patterns can produce strongly supralinear dendritic integration in RAD INs even though they have more simple, aspiny dendrites. This could lead to the enhancement of clustered distal inputs by taking advantage of local dendritic NMDA spikes, and therefore distal inputs might overcome dendritic signal attenuation and reach the axosomatic integration region (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study shows that clustered input patterns can produce strongly supralinear dendritic integration in RAD INs even though they have more simple, aspiny dendrites. This could lead to the enhancement of clustered distal inputs by taking advantage of local dendritic NMDA spikes, and therefore distal inputs might overcome dendritic signal attenuation and reach the axosomatic integration region (11).…”
Section: Resultsmentioning
confidence: 99%
“…Dendritic integration in principal cells is mediated by multiple layers of logical integrators (2,6,10), the first layer being the apical Ca 2+ and axonal Na + integration zone, generating relatively more global propagating spikes. At the same time, both tuft and basal thin dendritic branches are able to generate NMDA spikes, providing an integration method for distant inputs to overcome strong dendritic filtering (11) and drive the output of the cell (10). On the contrary, we are aware of no studies to date that have shown that local regenerative spikes (evoked or spontaneous) can occur in interneuron dendrites.…”
mentioning
confidence: 99%
“…In addition, we found that the amplitude of calcium activity is highly similar between different basal dendrites. This property indicates the output of the neuron is propagated robustly and uniformly throughout the entire basal compartment (9). Previous studies have further characterized subthreshold calcium activity in L2/3 basal dendrites as being organized into localized hotspot activity (26) that arises from single spine synaptic inputs (15,28).…”
Section: Discussionmentioning
confidence: 95%
“…These compartments are known to be specialized in terms of the type of synaptic input that they receive (7). Furthermore, in vitro studies of dendritic physiology have revealed several active dendritic signals in these compartments such as back-propagation of action potentials (bAPs) (8,9), NMDA spikes resulting from clustered synaptic activation (5), and calcium spikes initiated in the apical trunk (10,11). Despite the presence of these dendritic specializations, little is known about the importance of these features for in vivo function.…”
mentioning
confidence: 99%
“…If we have the full spatiotemporal voltage signal then it is possible to use straightforward statistical methods to infer many biophysical quantities of interest (Morse et al, 2001;Wood et al, 2004;Huys et al, 2006), such as passive cable parameters, active properties, and in some cases even time-varying information, such as the rate of synaptic input. Unfortunately, technical challenges limit multiple-electrode recordings from dendrites to only a few electrodes, typically targeted far from the tips of dendritic branches (Stuart and Sakmann, 1994;Cox and Griffith, 2001;Cox and Raol, 2004;Bell and Craciun, 2005;Petrusca et al, 2007;Nevian et al, 2007;Homma et al, 2009). High-resolution two-photon imaging techniques provide more spatially-complete observations, but with significantly lower signal-tonoise (Djurisic et al, 2008;Homma et al, 2009;Canepari et al, 2010Canepari et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%